1998
DOI: 10.1094/pdis.1998.82.10.1093
|View full text |Cite
|
Sign up to set email alerts
|

Seedborne Infection of Rice by Pyricularia oryzae and Its Transmission to Seedlings

Abstract: Seedborne infection of rice by Pyricularia oryzae and its transmission to seedlings were studied quantitatively with naturally infected seeds of three rice cultivars collected from three locations in Nepal. A linear relationship on a logistic scale was found between panicle symptoms and seed infection, i.e., the more symptoms the higher seed infection. However, healthy-looking panicles and branches of panicles could also yield infected seeds. Postharvest measures such as winnowing and sun-drying significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0
5

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 14 publications
4
31
0
5
Order By: Relevance
“…This high frequency has been reported in previous studies on the seeds of rice in India (Archana and Prakash, 2013) and Pakistan (Khan, 2000;Javaid et al, 2002 (Khan, 2000;Wahid et al, 2001;Javaid et al, 2002;Nguefack et al, 2007). In this study, Pyricularia oryzae, known for a long time as rice seed borne fungus (Manandadhar et al, 1998) was not isolated from any of the rice varieties, confirming the statement by Lamrani et al, (2013) who found that this fungus was less common on seeds. Aluko (1969) tested rice seed samples for seed borne fungi and indicated the scarcity of this fungus in Nigeria.…”
Section: Resultssupporting
confidence: 84%
“…This high frequency has been reported in previous studies on the seeds of rice in India (Archana and Prakash, 2013) and Pakistan (Khan, 2000;Javaid et al, 2002 (Khan, 2000;Wahid et al, 2001;Javaid et al, 2002;Nguefack et al, 2007). In this study, Pyricularia oryzae, known for a long time as rice seed borne fungus (Manandadhar et al, 1998) was not isolated from any of the rice varieties, confirming the statement by Lamrani et al, (2013) who found that this fungus was less common on seeds. Aluko (1969) tested rice seed samples for seed borne fungi and indicated the scarcity of this fungus in Nigeria.…”
Section: Resultssupporting
confidence: 84%
“…In the year 2001 P. oryzae was isolated in the 45.5% of the lots of certified seeds from the Marismas cultivars, 36% of Orellana and the 45.5% of Fonsa (Table 1). The presence of P. oryzae in the first two years is was not strange since although one of the channels of transmission of this disease is the seed, the scientific bibliography makes reference to that the habitual measures that receives the grain of rice once collected as the drying to the sun or in mechanical dryer, disqualify inoculum of this present agent in the seed (MANANDHAR et al 1998).…”
Section: Resultsmentioning
confidence: 99%
“…Despite the appearance of P. oryzae in 2001 in certified sowing seeds as much harvested grains makes you think that in previous years the cause of the absence of the pathogen in seeds was caused by the lack of inoculum or so that the environmental conditions were not the appropriate ones for the development of the disease. Also it is possible to emphasize that the smaller percentage of infection found in certified sowing seeds respecting to harvested grain can be consequence of the mechanical drying that disqualifies part of inoculo of this agent in the sowing seeds (MANANDHAR et al 1998). Although the wind is the main via for conidia dissemination of P. oryzae the seeds also considers an important channel of transmission (LEE 1994;OU 1987) of fytopathogenes fungi when these come from campaigns with a considerable level of inoculum and appropriate climatic conditions for the development of the disease, therefore are advisable to know the fytosanitary state of the seeds before being used for sowing time.…”
Section: Symptomatology Of the Injuries And Pathogenicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Rice blast is predominantly a leaf spot disease but under severe conditions, the panicle and grains can be affected (Ou 1985). Rice blast can become severe if blast susceptible cultivars are grown (Manandhar et al. 1998; Long et al.…”
Section: Introductionmentioning
confidence: 99%